Global public-private partnerships: part II - what are the health issues for global governance? - K. Buse; G. Walt
This is the second of a two-part review of global public-private partnerships (GPPPs) for health development. Part I was published in the April issue of the Bulletin (Vol. 78, No.4). The recent emergence of GPPPs is rapidly reconfiguring the international health landscape. While most multilateral and bilateral agencies are currently grappling with how to proceed, there is little information in the public domain concerning how individual partnerships work and to date very little consideration of the many implications of this trend. This paper differentiates between product-based, product development-based and issues/ systems-based GPPPs and describes a number of examples of each type in the health sector. The benefits of these initiatives, not least the major resources which they harness for specific health problems, are identified. The final section of the paper explores the implications and dilemmas posed by GPPPs. It discusses whether or not shared goals can transcend conflicting values and mandates and how governance of partnership arrangements may transform and undermine certain attributes of multilateral organizations. The paper concludes that the current climate of goodwill between public and private sectors offers an opportunity that should not be missed: it can be used not only to foster new partnership but to ensure that partnership is truly in the interests of international public health.